Drag Keats: Mark Doty's Cockney Poetics. Issue 3 (4th May 2017) - Eisner, Eric
ABSTRACT: In the American poet Mark Doty's books of the 1990s, allusions to Keats are so frequent and so pronounced as to make Keats appear a kind of presider to the poetry. Doty's lyrics may often be elegiac in tone, but his use of Keats is neither elegiac nor nostalgic. I see Doty's style in these early books as enacting a reading of the critical possibility of Keats's style, one that corroborates the insights of recent materialist scholarship on Keats. I understand Doty's queer poetics as strategically employing a kind of Cockney poetics. Where for many contemporary poets Keats functions as the icon of lyric tradition or authenticity of "experience, " Doty, working within the lyric tradition, connects Keats to drag, kitsch, and simulation. I propose D. W. Winnicott's notion of "object use" as a model for this irreverently allusive "use" of Keats.